2023
DOI: 10.3389/fpls.2023.1284235
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing window size and directional parameters of GLCM texture features for estimating rice AGB based on UAVs multispectral imagery

Jikai Liu,
Yongji Zhu,
Lijuan Song
et al.

Abstract: Aboveground biomass (AGB) is a crucial physiological parameter for monitoring crop growth, assessing nutrient status, and predicting yield. Texture features (TFs) derived from remote sensing images have been proven to be crucial for estimating crops AGB, which can effectively address the issue of low accuracy in AGB estimation solely based on spectral information. TFs exhibit sensitivity to the size of the moving window and directional parameters, resulting in a substantial impact on AGB estimation. However, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Topography Slope Slope in degrees / Elevation Elevation above sea level in meters / P ij represents the probability of each pixel pair (i, j) value and i, j are the gray tones in the windows, which are also the coordinates of the co-occurrence matrix space; N represents the number of distinct grey levels in the quantized image, which has a gray value range of the original image [54].…”
Section: Feature Extraction From Optical Images In Vegetated Areasmentioning
confidence: 99%
“…Topography Slope Slope in degrees / Elevation Elevation above sea level in meters / P ij represents the probability of each pixel pair (i, j) value and i, j are the gray tones in the windows, which are also the coordinates of the co-occurrence matrix space; N represents the number of distinct grey levels in the quantized image, which has a gray value range of the original image [54].…”
Section: Feature Extraction From Optical Images In Vegetated Areasmentioning
confidence: 99%
“…Guo et al [60] discovered that Con had the highest accuracy in extracting maize heading date. Liu et al [23] demonstrated that Con outperformed other Tm in estimating rice above-ground biomass (AGB). The study's optimal TFCI D and TFCI T treatments primarily consisted of Mea, Cor, Con, and Dis.…”
Section: Contribution Of Texture Information To Lnc Estimation Across...mentioning
confidence: 99%
“…They show the parts of the plant growing quickly and consistently, documenting the developmental variations in wheat at various growth stages. Con and Dis focus on high-frequency information, demonstrated by Liu et al [23] to help estimate crop information, such as the degree of gray-level fluctuations and the relationship between pixel distances and diagonal. Sensitive Tm enhanced the response to LNC across multiple growth stages by employing feature combination formulas, which reflected the changes in LNC over these times.…”
Section: Contribution Of Texture Information To Lnc Estimation Across...mentioning
confidence: 99%
See 1 more Smart Citation
“…These dimensionless indices integrate spectral data from different narrow-band wavelengths and can reflect characteristics including coverage, chlorophyll content, moisture, and health status ( Bannari et al., 1995 ). Along with VIs that make use of spectral features, texture indices that reflect subtle variations in canopy structure are also commonly used to enhance the estimation of AGB ( Wang et al., 2022b ; Liu et al., 2023a ). Many studies predominantly focus on establishing empirical relationships directly between these features and ground-measured AGB values using statistical analysis and machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%